Review of the Irish and international literature on health and social care unit cost methodology - Richard Whyte; Conor Keegan; Aoife Brick; Maev-Ann Wren (The Economic and Social Research Institute (ESRI), 2018)
This literature review examines the methodologies used to calculate health and social care unit costs internationally and in Ireland. The purpose of this review is to identify the alternative approaches to unit costing for health and social care services in the literature and to assess the advantages and disadvantages of their use in an Irish context. The review finds that the use of bottom-up or top-down methods varied by type of study being undertaken. The proportion of studies that used unit costs calculated by applying a bottom-up approach was higher than the proportion using a top-down approach. Bottom-up approaches dominated when there was a greater need for accuracy in estimates, such as in health technology assessments, or when the extra data requirements of the bottom-up approach were not too penalising, such as with disease/setting specific studies. Top-down approaches were prevalent among studies that needed to estimate unit costs across a wide range of services and diseases. Top-down approaches were also more prevalent than bottom-up approaches for projection models of health and social care that used unit costs. At present, the Irish system suffers from the lack of a centralised unit, like the PSSRU in England, tasked with producing annual volumes of unit costs for health and social care. The development of comprehensive unit cost profiles for Irish health and social care services would be of significant benefit to researchers, policymakers and wider health system stakeholders.
Keywords: 330